Solid Decanter-AMF Biostimulation for Oil Palm Nursery Development on Ex-iron Mining Land - Adrinal Adrinal; Yesi Widia; Elsa Loita Putri; Edwin Edwin; Gusmini Gusmini (Institut Pertanian Bogor, 2026)
This study investigates the impact of decanter solid and arbuscular mycorrhiza on the growth of oil palm seedlings in pre-nursery on ex-iron ore mining sites. The construction of pits during iron mining has resulted in soil degradation and abandonment. The addition of solid decanter and arbuscular mycorrhiza can improve the chemical characteristics of soil. The study sought to determine the interaction between solid decanter and arbuscular mycorrhiza, as well as the optimal dose of solid decanter and arbuscular mycorrhiza for oil palm seedling growth in the pre-nursery. This study employed a factorial Completely Randomized Design with two factors and four treatment levels. The first factor was solid decanter (0, 200, 300, and 450 g), whereas the second was arbuscular mycorrhiza (0, 5, 10, and 15 g/polybag). The parameter studied included initial soil analysis, solid decanter analysis, final soil analysis, seed height, stem diameter, number of leaves, leaf length, fresh and dry seedling weights. The study's findings revealed an interaction between solid decanters and arbuscular mycorrhiza on leaf length, fresh weight, and dry weight of seedlings. The treatment dose of 450 g solid decanter and 5 g/polybag arbuscular mycorrhizae resulted in the best growth in all variables. Keywords: arbuscular mycorrhizae, fertility, mycorrhiza, pre-nursery